Percepção de educadoras sobre crianças com autismo na educação infantil - Nascimento, Laura Lima do (Universidade Federal de São Carlos, 2024)
The early childhood education stage plays a fundamental role in global development in early childhood and the interpersonal relationships established within the school environment in the first years of schooling, especially with regard to the teacher's role, affect the student's performance. This study aimed to identify, through dialogues with regular classroom teachers and special educators, the perceptions regarding the coexistence of children with ASD in the regular classroom and the interpersonal relationships that occur in the school environment. A qualitative approach was used, using a semi-structured interview guide. Four common room teachers and two special educators participated in the research. The results obtained allow us to infer that educators independently search for information about ASD, according to their demands within the school environment; Furthermore, teachers' perception of the presence of children with ASD in early childhood education has been changing in a positive and significant way, mainly due to greater access to information and contact with special educators within schools.
Educators’ perception of children with autism in early childhood education
Keywords: Educação especial; Transtorno do espectro do autismo; Educação infantil; Special education; Autism spectrul disorder; Early childhood education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL